Διεθνής Σημειωτική Εταιρεία (IASS-AIS) - (:unkn) unknown (My University, 2026)
The International Association for Semiotic Studies (IASS) is a global scholarly organization of researchers studying processes and systems of signification and communication, not only in social life and everyday worlds but also in biological and zoological contexts. Semiotics is a discipline that cares about how meaning and communication are created and understood in the natural and cultural environments of all kinds of beings — human and non-human alike. Semioticians employ rigorous methods and tools that allow them to inquire meaning, to propose explanatory models, and highlight the diverse possible interpretations of any given phenomenon. As such, semioticians serve as “mediators” between disciplines, professions, and individuals interested in the significance of life and the world around them. http://iass-ais.org